The horse would know, but the horse can't talk : Giovani artisti italiani - premio Querini Stampalia - FURLA per l'arte. - FURLA per l'Arte, Bologna; Auregli, Dede; Beccaria, Marcella; Bertola, Chiara; D'Orazio, Costantino; De Cecco, Emanuela; Di Pietrantonio, Giacinto; Frisa, Maria Luisa; Kohlmeyer, Agnes; Maloberti, Marcello; Maraniello, Gianfranco; Mocellin, Ottonella; et al. (Milano : Edizioni Charta, 2002)
This volume bears witness to the third edition of the Premio Querini Stampalia - FURLA per l'arte. The prize was conceived by Chiara Bertola, in consultation with Giacinto Di Pietrantonio and Angela Vettese, to document and honor emerging artists who live and work in Italy. After a meticulous examination of works by young contemporary artists, the national jury selected, as always, five finalists : Marcello Maloberti, Ottonella Mocellin, Adrian Paci, Daniele Puppi and Sissi. Following Kosuth and Kabakov, the "godfather" of this third edition of the prize is the German artist Lothar Baumgarten, who has invented a complex and unusual play on words, a proverb that invites us to reflect on the impossibility of judging an artist : "the horse would know, but the horse can't talk".
Maloberti, Marcello ; Mocellin, Ottonella ; Paci, Adrian ; Puppi, Daniele ; Sissi ; A 12 ; Borghi, Enrica ; Canavacciuolo, Maurizio ; Levita, Mariangela ; Andrini, Alessandra ; Dafni & Papadatos ; Gennari, Francesco ; Pintaldi, Cristiano ; Sassi, Corrado ; Benassi, Elisabetta ; Caravaggio, Gianni ; Kinkaleri ; Pancrazzi, Luca ; Previti, Riccardo ; Cariello, Letizia ; Bello, Paola Di ; Giliberti, Eugenio ; Papa, Marco ; Sartori, Maria Teresa ; Benvenuto, Carlo ; Cecchini, Loris ; Matteo, Gabriele Di ; Miura, Yoko ; Tuttofuoco, Patrick ; Bramante, Davide ; Carlisi, Rocco ; Favelli, Flavio ; Galegati, Stefania ; Simeti, Francesco ; Berrettini, Marco ; Golia, Piero ; Motti, Gianni ; Vitali, Massimo ; GAHP (Genetic Art History and Promotion) ; Matto, Mario & C. ; OPU (Operazioni di Pubblica Utilità) ; Pellegatta, Leo ; Tessarollo, Silvano ; Mangano, Domenico ; Perrone, Diego ; Scotto di Luzio, Lorenza ; Losi, Claudia ; Pellegrini, Nicola ; Spranzi, Alessandra ; Vaglieri, Marco
biog., ind. tent., gr. tent., perf., videog. p. 58-59, bibliog. p. 60-61
Engels & Italiaans
The horse would know, but the horse can't talk : Young Italian Artsts, Fondazione Querini Stampalia, Venezia, 24 March - 19 May 2002
kunstcatalogus
Keywords: Italië